IMPLEMENTATION OF PUBLIC INFORMATION DISCLOSURE POLICY ON REGIONAL DEVICE ORGANIZATIONS IN BANTEN PROVINCE DURING THE COVID-19 PANDEMIC - Toni Anwar Mahmud (Pro Patria: Jurnal Pendidikan, Kewarganegaraan, Hukum, Sosial, dan Politik, 2023)
ABSTRACT The purpose of this study was to see how the implementation of policies that support the disclosure of public information on the Banten Provincial Government Regional Apparatus during the Covid-19 pandemic. The research method used in this study is a qualitative research method with a descriptive analysis approach. Disclosure of public information which is an obligation of public bodies, especially regional apparatus in Banten Province during the Covid-19 pandemic is still found to be very minimal in conveying public information that must be announced so that communication between the government and the public is hampered. While the Banten provincial government already has various channels for delivering public information such as www.bantenprov.go.id, jawara e-gov on android applications, there is still a lack of public information that guarantees citizens' rights to know various plans and programs for public policymaking, such as the lack of public information on who is the recipient of social assistance during Covid-19; the lack of public information makes the community's active role in public policy-making not accommodated; the decline in good state administration, so that the public lacks public information to find out various reasons for public policies that affect the lives of many people.